Strengthening village democracy; proceedings of national conference on Gram Sabha / edited by R. C. Choudhury and S. P. Jain - National Institute of Rural Development (Hyderabad, 1999)
This book deals with rural development
Keywords: "Rural development-conference July, 28-29, 1999"